2021
DOI: 10.1038/s41467-021-20932-y
|View full text |Cite
|
Sign up to set email alerts
|

Perception of a divergent family of phytocytokines by the Arabidopsis receptor kinase MIK2

Abstract: Plant genomes encode hundreds of receptor kinases and peptides, but the number of known plant receptor-ligand pairs is limited. We report that the Arabidopsis leucine-rich repeat receptor kinase LRR-RK MALE DISCOVERER 1-INTERACTING RECEPTOR LIKE KINASE 2 (MIK2) is the receptor for the SERINE RICH ENDOGENOUS PEPTIDE (SCOOP) phytocytokines. MIK2 is necessary and sufficient for immune responses triggered by multiple SCOOP peptides, suggesting that MIK2 is the receptor for this divergent family of peptides. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 53 publications
5
86
0
3
Order By: Relevance
“…10a ). Our study is consistent with an accompanying report in which MIK2 was identified as a receptor of plant SCOOPs and mediated response to Fusarium SCOOP-like peptides 47 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…10a ). Our study is consistent with an accompanying report in which MIK2 was identified as a receptor of plant SCOOPs and mediated response to Fusarium SCOOP-like peptides 47 .…”
Section: Discussionsupporting
confidence: 93%
“…In Fusarium spp., the SCOOPL motif we identified is located in the N-terminus of a highly conserved GAL4 DNA-binding domain-containing protein with uncharacterized functions. It is possible that SCOOPL motifs are also present in some other proteins in Fusarium spp 47 . Some of these SCOOPLs are active in triggering MIK2- and BAK1/SERK4-dependent immune responses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The salthypersensitive phenotype of mik2 mutant can be suppressed by the1-1, a null mutation of THE1 [134]. Recently, the serine rich endogenous peptide (SCOOP) phytocytokines were identified as the ligands of MIK2 to trigger immune responses [135], but whether the SCOOP peptides participate in MIK2-mediated regulation of salt tolerance is still unknown. FEI1 and FEI2 are two LRR-RLKs that are associated with cellulose synthesis and anisotropic cell expansion and are involved in CWI sensing [136].…”
Section: Cell Wall Integrity Sensing and Signal Transduction Under High Salinitymentioning
confidence: 99%
“…Recientemente, el péptido SSP8 ha sido descrito como PROSCOOP5 y se ha demostrado que su expresión se induce con el tratamiento de O3 y la infección con PsPto y B. cinerea (Gully et al, 2019). Cabe destacar que otro miembro de la familia, SCOOP12, ha demostrado tener un papel relevante en la inmunidad y actuar como una fitocitoquina en Arabidopsis a través del receptor MIK2 (Gully et al, 2019;Rhodes et al, 2021).…”
Section: Discussionunclassified
“…La sobreexpresión de prePIP1 y prePIP2 o aplicación exógena de PIP1 y PIP2 resultaron en una mayor resistencia de Arabidopsis a patógenos. Tanto AtPep1 como PIP1 son capaces de amplificar la respuesta inmunitaria desencadenada por flg22 y aumentar la resistencia frente a la bacteria PsPto y al hongo Fusarium oxysporum (Hou et al, 2014 (Gully et al, 2019;Rhodes et al, 2021).…”
Section: Aminoácidos Extracelulares Y Glutatiónunclassified